Kajian Pemodelan Kemudi Kapal Pengawas Tanpa Awak - Naufal Abdurrahman; Sapto Wiratno Satoto; Hardi Radesha (Politeknik Negeri Batam, 2015)
Unmanned surveillance vessels on operational conditions required to move quickly and to maneuver skillfully. The steering system is one of the mechanical devices used to determine and to able the vessel maneuvering and directed to a specific location or destination. Some things that affect agility maneuver the vessel on the water surface is form of the hull and rudder conformity with the shape of hull. Leaves the wheel is not suitable for a particular vessel size provide an enormous influence on the vessel at the time of sailing. This study aims to model the optimal steering system according to the shape of unmanned surveillance’s hull so as to support the operation of the vessel's performance. An advanced approach to the design of the model is divided three stage process, i.e: concept design, initial design and detailed design.